Transformation of the Theory of Financial Recovery of the Organization as a Factor in Improving the Rehabilitation Effectiveness of Bankruptcy Procedures - E. Р. Kochetkov (Финансы: теория и практика, 2024)
The purpose of the study is to change the current methodology for identifying the fundamental aspects of an organization’s financial recovery by analyzing the elements that are needed for the theory of financial recovery to change under current conditions.   The subject of the study is the financial and economic mechanisms for the settlement of overdue debts of insolvent organizations in out-of-court and judicial (under bankruptcy procedures) regimes within the framework of financial relations with creditors.   The relevance of the work is due to theoretical and practical problems.   The strengthening of the factors of the business crisis against the background of a high debt burden and low economic growth significantly increases the risks of mass bankruptcies of organizations, which requires the improvement of financial recovery tools. However, the existing paradigm of the theory of financial recovery is focused on preventing threats to the property interests of the owners of the debtor organization — this reduces the rehabilitation potential of such a theory. Analysis of the implementation of bankruptcy procedures in Russia shows the inefficiency of rehabilitation and liquidation procedures, which in most cases end in the liquidation of the organization and the separate sale of its assets in parts. Using logical research methods (analysis, synthesis, induction), economic analysis of judicial statistics on bankruptcy in Russia and the USA, methods of economic comparison and the provisions of the systematic approach, the theory of corporate reorganization of L. Bebchuk, the contract theory of the firm O. Hart and the theory of crisis management of socio-economic systems, the original results of the study were obtained. The article proposes to change the object composition of the processes of financial recovery: to shift the emphasis from protecting the property interests of the debtor organization to preserving its business from destruction. The change in the object composition provides, among other things, a solution to the key strategic problem of the institution of bankruptcy — finding a balance between rehabilitation and liquidation procedures, preventing the preservation of inefficient and liquidation of effective debtors.   The orientation of financial recovery tools to preserve businesses from destruction allows us to develop provisions on the risk of bankruptcy of organizations and increase the rehabilitation potential of bankruptcy liquidation procedures, which determines the novelty of the study.